Forgive us our sins: a critical perspective of Corporate Social Irresponsibility (CSiR), insights from the case of the Samarco mining dam collapse in Brazil - Pereira, Jussara Jéssica (2021)
This dissertation consists of a set of three articles on the social-environmental disaster caused by the Samarco mining dam collapse, in Brazil. These articles take arguments and constructs based on management history, memory and forgetting to problematize the veiled dimensions of Corporate Social Irresponsibility (CSiR). Over the past years, we have seen many ethical scandals in organizations, becoming more frequent. Since the early-2000s, studies on CSiR have been gathering more attention in management and organization studies. We already know about its negative impact on society and business. However, we still have a limited understanding of what exactly CSiR is. Analyses that consider contradictory versions, facts, and conditions of CSiR are still scarce. I investigate how can companies shape future perceptions of their involvement in CSiR. Through empirical research, I observe relationships between mining companies and local communities in areas impacted by CSiR. In the first article, I investigate why some of the victims and stakeholders began to minimize their criticism of companies, after an incident involving corporate irresponsibility. In the second article I question, how companies may strategically deploy misinformation around an episode of corporate irresponsibility. Finally, in the third article, I discuss how some versions of the past appear more powerful, legitimate, and credible than others. My results show that due to the strong economic role that the extractive industry plays in the region, (1) the mining company has developed a quasi-parental relationship with the municipality, generating employment, contributing to the economy, improving access to consumer goods, and culture, among others, thereby driving the municipality to one of the highest GDP per capita in the state of Minas Gerais, ranking among the 100 municipalities with the highest GDP per capita in Brazil - in the year before the dam collapse. In contrast, (2) the mining company has also manipulated information concerning the security of its operations, ignoring risks and community safety. This situation caused chaos, uncertainty, controversy, and a lack of information in the worst affected city. I conclude my argument by pointing out that due to the concentrated power of the extractive industry in the region, (3) the mining company has been trying to articulate a new version of the narrative for its future. For the company and pro-company stakeholders the collapse is a kind of blessing and everything will be better in the future. Nevertheless, uncertainty and doubt remain on how the company will compensate the victims for all their losses, and for some of them, this is an unfulfilled promise. By showing these results, I am generating insights to inform a theory of Corporate Social Irresponsibility. With a historically oriented analysis, I am contributing to a deeper understanding of the strategic uses of the past by organizations in their narratives.